Multiaxial fatigue behaviors of 2024-T4 aluminum alloy under different corrosion conditions. (May 2017) - Chen, Yajun; Liu, Chenchen; Zhou, Jian; Wang, Xianchao
Graphical abstract: Highlights: Aircraft in-service environment simulation by alternate corrosion-fatigue tests. Pre-corrosion reduces material's multiaxial fatigue life. Life decreases with increase of either unit corrosion time or unit loading cycle. Cracks initiate at specimen surface and corrosion morphology can be observed. Life prediction is made based on pre-corroded test and Miner's rule. Abstract: In order to study multiaxial fatigue behavior of 2024-T4 aluminum alloy with an aircraft in-service environment, fatigue tests of multiaxial pre-corrosion and alternate corrosion are carried out. With the extension of pre-corrosion time, the multiaxial fatigue life decreases under the same equivalent stress. Pitting caused by corrosion is observed on the surface of specimens. While pre-corrosion time increases, the number and size of pits become larger and connection between adjacent corrosion pits becomes more obvious. For the multiaxial fatigue tests with alternate corrosion, for the same unit corrosion time, the fatigue life decreases with the increase of unit loading cycles. Under the same unit loading cycles, the fatigue life decreases as the unit corrosion time increases. The cyclic hardening appears in both axial and tangential directions at the initial loading stage. Cyclic softening trend becomes obvious as the number of alternation increases. It is shown that cracks initiate at specimen surface and gradually extend to inside. Exfoliation corrosion morphology can be observed on specimen surface. Based on Miner's rule and data of pre-corroded multiaxial fatigue test, the alternate corrosion-multiaxial fatigue lives are predicted.